MENGGALI PELUANG AKUNTAN MASA DEPAN: PENGENALAN PROFESI UNTUK SISWA SMK DI SEMARANG - Setyowati, Widhi; Solovida, Grace Tianna; Kusuparwati, Yohana; Setiyono, Taufiq Andre (Fokus ABDIMAS, 2024)
The accounting profession plays a crucial role in supporting national economic growth and ensuring stability in political, economic, and cultural aspects. To introduce the significance of this profession to younger generations, a community service activity was held at SMK Cut Nya’ Dien in Semarang on August 12, 2024. The activity aimed to educate students on the importance of accounting in business, as well as the opportunities and challenges faced by accountants in the future. The method used included interactive lectures and two-way discussions, encouraging active participation from 20 grade 12 students. The materials covered the role of accounting in business management, career opportunities in accounting (public accountant, management accountant, audit, taxation), and the challenges accountants face in the digital era. Student understanding was evaluated through quick quizzes and a "fishing" technique to stimulate discussion. Door prizes were also given to motivate active engagement. This activity successfully enhanced students' understanding of the accounting profession. Keywords: Accounting profession, career opportunities, student engagement